Analysis of Comparative Studies of Political Gerontocracy in the World of the United States, Africa, Venice, Turkey - Pugu, Melyana R (Faculty of Law, Universitas Pekalongan, 2024)
The purpose of this study is to find out the Analysis of Comparative Studies of Political Gerontocracy in the World of the United States, Africa, Venice, Turkey. Because these four countries have geopolitics that are very interesting, we know it as a study for other governments. The method of this research is In this study, the author optimally uses two data sources related to this research, namely. Primary data sources and secondary data sources. The main source of this research is books and scientific journals on Political Gerontocracy in the World. At the same time, this research is supported (secondary) by other works of thought related to politics in the United States, Africa, Venice, Turkey. The results of this study that gerontocracy can provide political stability and wisdom in decision-making such as gerontocracy in the United States brings benefits in terms of stability and experience, but also poses a major challenge related to policy relevance. Then gerontocracy in Africa created long-term stability in some countries, but also hampered dynamic political, economic, and social development. While many senior leaders are considered historical figures and have great influence. The continued gerontocracy in Italy creates challenges for a more dynamic and diverse leadership regeneration. However, with support for reforms from young people and pressure to create more inclusive policies, Italy has an opportunity to improve its political system. And the gerontocracy in Turkey provides stability in the face of major challenges, but it also brings obstacles to political regeneration and policy innovation.